IMPLEMENTASI ONE HOUR NOTICE (OHN) OLEH PERWIRA JAGA DI MT.PIS PATRIOT - Zeni Hesinovita; Arya Widiatmaja; Rizal Rochmansyah; Rosnani (STKIP Subang, 2026)
One Hour Notice (OHN) is a critical procedure in ship operations designed to ensure readiness before the vessel conducts maneuvering activities such as departure, berthing, or handling conditions requiring heightened alertness. The implementation of One Hour Notice (OHN) requires effective coordination between deck and engine watchkeepers to ensure that all steps are carried out according to operational standards. This study aims to evaluate the watchkeeping officers’ understanding of the OHN procedure and assess its implementation on board MT. Pis Patriot, as well as identify potential obstacles encountered during its execution. This research employs a descriptive qualitative method supported by observation, structured interviews, and documentation. Informants include deck watch officers, engine watch officers, and the Chief Engineer. The research instruments consist of observation sheets, interview guides, and documentation checklists. Data were analyzed using the stages of data reduction, data display, and conclusion drawing based on the Miles and Huberman model. The results indicate that the officers’ understanding of One Hour Notice (OHN) falls into the “fairly good” category, although several inaccuracies remain regarding specific objectives and procedural sequences. The implementation of One Hour Notice (OHN) on board is generally effective but not yet fully consistent, particularly concerning time synchronization, inter-department coordination, and the completion of inspection checklists. Main obstacles include limited training, outdated SOPs, and insufficient routine evaluations by ship management. Overall, this study concludes that although One Hour Notice (OHN) implementation on MT. Pis Patriot is functioning adequately, improvements in theoretical understanding and procedural compliance are needed to fully support ship safety and operational efficiency.